CRISPR mutant rapid identification in B. napus: RNA-Seq functional profiling and breeding technology application - Geng, Rui; Fan, Xiang; Sarwar, Rehman; Wang, Yong; Dong, Ke; Tan, Xiao-Li (Frontiers in Plant Science, 2025)
IntroductionTraditional rapeseed breeding is inefficient and imprecise. CRISPR genome editing offers a precise alternative for trait improvement. Here, we edited the Bnaida gene in elite rapeseed cultivar ZS11 to study its role in floral organ abcission and enable rapid trait transfer to elite lines.MethodsThe BnaIDA gene was CRISPR-edited in ZS11. Phenotypes (petal adhesion time, cracking force of siliques) were statistically analyzed. And analyze the mutants using RNA -Seq. Edited alleles were introgressed into elite line SW1-6 via backcrossing. Locus-specific primers enabled efficient genotyping to distinguish hetero- and homozygous plants during selection.Results and discussionIn this study, The Bnaida mutant by gene editing in the cv ZS11, which is widely used in rapeseed breeding. The phenotypic analysis showed that the petal was attached to the pod and pods were harder to crack in edited plants, and then we quickly introduced two Bnaida loci into the elite line of SW1-6 by backcrossing with edited ZS11 as the donor plant. Locus-specific primer combinations were designed to differentiate heterozygous and homozygous genotypes in backcrossing generations, enabling efficient and rapid selection. This study highlights the integration of gene editing and genotyping selection, offering insights into the future of gene editing-assisted breeding.